Progressive hemiparesis in a young man: Hemicerebral atrophy as the initial manifestation of basal ganglia germinoma - Woo, Peter; Chu, Alberto; Chan, Kwong; Kwok, John (Asian Journal of Neurosurgery, 2017)
Basal ganglia germinomas are rare and patients are classically young Oriental males presenting with gradually progressive hemiparesis. Although early treatment with chemo-radiotherapy can be curative and significantly improve the quality of life, medical attention is often delayed. A young Chinese male experienced a 6-month history of right hemiparesis with magnetic resonance imaging findings of hemicerebral atrophy and lentiform nucleus microhemorrhage, highly suggestive and early signs of basal ganglia germinomas. No further imaging was performed until 2 years later when he was admitted for acute neurological deterioration and a repeat scan revealed a large infiltrative tumor pathologically confirmed to be a pure germinoma.
Keywords: Basal ganglia germinoma; cerebral hemi-atrophy; gradient echo imaging; hemicerebral atrophy; Wallerian degeneration